Investigation into the Challenges Facing Planning of Mathematic Programme in Senior Secondary Education in Abuja, Nigeria. - Ogunode Niyi Jacob (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2020)
The aim of this study is to investigate the challenges facing the planning of mathematics programme in Federal Capital Territory, Nigeria. The study adopted descriptive research survey design. The population of the study comprised ninety (90) respondents. Stratified and systematic sampling technique was used to select the sample population. The study employed the used of questionnaire as instrument for data collection. Two lecturers from Educational Administration and planning from University of Abuja was consulted to validate the questionnaire. Three research questions and two hypotheses were developed for the study. Test-retest reliability was employed for the study. Percentage and Chi-square test was used to test the hypotheses and data collected from the study. The result revealed that there are challenges facing the planning of mathematics programme of senior secondary education and the challenges includes; inadequate data/information to plan, inadequate funding of planning of mathematics programme, poor capacity development of few mathematics planners, inadequate professional mathematics planners ,political instability, corruption and lack of political will to support planning of mathematics education. The study concluded that the implication of the challenges on the implementation mathematics education is poor implementation of the mathematics programme in the senior secondary schools. The study recommends that the government should increase the funding of educational planning in the country especially mathematics education.